Highly Efficient Defluoridation of Water through Reusable poly(aniline-co-o-aminophenol) Copolymer Modified Electrode Using Electrochemical Quartz Crystal Microbalance. Issue 2 (17th February 2021) - Unal, Asuman; Hillman, A. Robert; Ryder, Karl S.; Cihangir, Salih
Abstract : Although the World Health Organization (WHO) recommends a limit of 1.5 mg l −1 fluoride ions in drinking water, this is not satisfied in many parts of the world. When this limit is exceeded, the electrochemically switched ion-exchange (ESIX) technique (mainly based on conductive polymers) has been identified as a promising method for removing the excess fluoride ions. The present study aimed to develop an efficient method based on the ESIX technique by using poly(aniline-co- o -aminophenol) copolymer to extract fluoride ions. Electrochemical quartz crystal microbalance (EQCM) and acoustic admittance data were utilized to assay the synthetic efficiency of copolymer deposition, and to evaluate the dependence of the defluoridation process on the proportions of the monomers in the copolymer matrix and on film thickness. The resulting films were characterised by Fourier transform infrared spectroscopy (FTIR) and scanning electrochemical microscopy (SEM) techniques. For optimized co-monomer ratio in the feedstock, poly(aniline-co- o -aminophenol) at an applied potential of 0.30 V showed excellent performance for fluoride removal from water at pH 6.6, to the extent of 20 (mg F − ) (g polymer) −1 . Comparison of the performance of ESIX using poly(aniline-co- o -aminophenol) with that of other techniques and materials reveal that it has significant potential for water defluoridation.